Jew among Jews : rehabilitating Paul - Ambrose, Kimberly (Eugene, Oregon : Wipf & Stock, 2015)
"Misunderstanding of Paul had started already in his lifetime, and his letters offer many examples of this. Throughout the centuries, Paul has continued to be misunderstood by both Jews and Gentiles, especially in relation to his view of the law and the covenant. Paul has often been misunderstood because his form of argument, his use of Scripture, his view of Jews and Gentiles in Christ (especially of those Jews who were not convinced that Jesus was Messiah), and his view of what constitutes true Judaism do not seem to conform to our expectations and perceptions of the apostle. We have been accustomed to read his letters as of one who was emancipating people from Judaism, as one who sought to obliterate all ethnic and other distinctions rather than maintaining the identity of Jews and Gentiles even in Christ. By building on some of the insights of the New Perspective, and developing other more recent insights as well, a more consistent and credible Paul as a first-century Diaspora Jew organizing a mission to Gentiles will be presented."--Back cover.
Includes bibliography (pages 187-205) and indexes.
Print version record.
Includes bibliographical references.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Theology; Paul, -- the Apostle, Saint; Bible; Judaism (Christian theology) -- History of doctrines -- Early church, ca. 30-600.; RELIGION / Biblical Studies / New Testament; RELIGION / Biblical Studies / Paul's Letters; Criticism, interpretation, etc; Electronic books